Total phenolic content and free radical scavenging activity of representative medicinal plants of Thailand - Chaiyavat Chaiyasut (2018)
© 2017 The Authors. Objective: Plants are the vital source of pharmaceutically important compounds with less or no adverse side effects. The current study was conducted to catalog the commonly used indigenous and medicinal plants of Thailand based on their phenolic acid content and antioxidant activity. Methods: The herbs were collected from Chiang Mai province, Thailand. The plants were extracted with 70% ethanol. The total phenolic acid content and antioxidant activity were evaluated. Results: The ethanolic extract of plant samples was prepared. Among the tested plant samples, Phyllanthus emblica Linn. and Terminalia belerica Roxb. showed highest phenolic content (Gallic acid equivalent [GAE]; 764.81 mg GAE/g sample) and antioxidant activity (trolox equivalent antioxidant capacity [TEAC]; 394.20 mg/g sample), respectively. About 94-97% of inhibition of free radical was detected in 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay tested against the plant samples. The ethanolic extract of Anaxagorea luzonensis Gray., Terminalia sp., T. belerica Roxb, Terminalia chebula Retz., Albizia procera Benth., Harrisonia perforata Merr., and P. emblica Linn. exhibited 97.87, 96.08, 92.26, 86.74, 86.08, 84.47, and 83.13% of superoxide radical inhibition, respectively. Conclusion: The results suggested that T. belerica Roxb. possessed high TEAC ability and DPPH radical scavenging capacity and A. luzonensis Gray. exhibited high superoxide scavenging activity, when compared to that of the other tested samples. The additional detailed study is desirable to understand the complexity and distribution of bioactive compounds present in the commonly used plant species of Thailand.